Effectiveness of a Very Low Calorie Ketogenic Diet on Testicular Function in Overweight/Obese Men - Mongioì, Laura M. (Nutrients, 2020)
Background: Obesity has become an increasingly worrisome reality. A very-low-calorie ketogenic diet (VLCKD) represents a promising option by which to achieve significant weight loss. This study sought to evaluate the effectiveness of VLCKD on metabolic parameters and hormonal profiles of obese male patients. Methods: We enrolled 40 overweight/obese men who consumed VLCKD for at least eight weeks. Body weight, waist circumference, fasting glucose, insulin, total cholesterol, high-density lipoprotein, triglycerides, creatinine, uric acid, aspartate aminotransferase, alanine aminotransferase, vitamin D, luteinizing hormone (LH), total testosterone (TT), and prostate-specific antigen (PSA) were calculated before and after VLCKD consumption. We additionally determined the homeostasis model assessment index and low-density lipoprotein (LDL) values. Results: After VLCKD (13.5 ± 0.83 weeks), the mean body weight loss was 21.05 ± 1.44 kg; the glucose homeostasis and lipid profile were improved significantly; serum vitamin D, LH, and TT levels were increased and the PSA levels were decreased significantly as compared with pretreatment values. These results are of interest since obesity can lead to hypogonadism and in turn, testosterone deficiency is associated with impaired glucose homeostasis, metabolic syndrome, and diabetes mellitus. Moreover, a close relationship between obesity, insulin resistance, and/or hyperinsulinemia and increased prostate volume has been reported, with a consequent greater risk of developing lower urinary tract symptoms. Conclusions: VLCKD is an effective tool against obesity and could be a noninvasive, rapid, and valid means to treat obese patients with metabolic hypogonadism and lower urinary tract symptoms.